Cooperative STBC with fuzzy election applied to surveillance wireless video sensor networks. (7th September 2011) - Sousa, Marcelo Portela; Lopes, Rafael Fernandes; Kumar, Ajey; Lopes, Waslon Terllizzie Araújo; de Alencar, Marcelo Sampaio
Wireless video sensor networks (WVSN) have been envisioned for a wide range of important applications such as video surveillance, emergency response, environmental and habitat monitoring. Transmitting video over WVSN requires large bandwidth as well as lifetime of sensor nodes long enough to fulfill the application requirements. This paper proposes an integrated system for WVSN (mainly used for surveillance) that combines the use of adaptive cooperative diversity and fuzzy logic. The cooperative spacetime block codes (STBC) are used to achieve full diversity with a simple maximum-likelihood decoding algorithm in order to enhance the performance of the considered WVSN. The performance comparison between the proposed system and a non-cooperative scheme is presented based on network lifetime, quality of transmitted videos, and required number of retransmissions under varying propagation scenarios in a WVSN. Simulation results show better performance for the proposed system, presenting greater lifetime, higher peak signal-to-noise ratio (PSNR) values of transmitted videos and lower propagation delay.